Purinergic modulation of glutamate transmission: An expanding role in stress-linked neuropathology. (October 2018) - Mayhew, J.; Graham, B.A.; Biber, K.; Nilsson, M.; Walker, F.R.
Highlights: Purinergic signalling from neurons and glia are utilised to modulate glutamate transmission. Astrocytes and microglia monitor glutamate levels as indicators of synaptic activity and tissue insult. Stress is recognised to negatively affect glutamatergic signalling and glial function. Further investigation into how stress affects purinergic control of glutamate is required. Abstract: Chronic stress has been extensively linked to disturbances in glutamatergic signalling. Emerging from this field of research is a considerable number of studies identifying the ability of purines at the pre-, post-, and peri-synaptic levels to tune glutamatergic neurotransmission. While the evidence describing purinergic control of glutamate has continued to grow, there has been relatively little attention given to how chronic stress modulates purinergic functions. The available research on this topic has demonstrated that chronic stress can not only disturb purinergic receptors involved in the regulation of glutamate neurotransmission, but also perturb glial-dependent purinergic signalling. This review will provide a detailed examining of the complex literature relating to glutamatergic-purinergic interactions with a focus on both neuronal and glial contributions. Once these detailed interactions have been described and contextualised, we will integrate recent findings from the field of stress research.